2015
DOI: 10.1007/s00384-015-2216-8
|View full text |Cite
|
Sign up to set email alerts
|

Emergency resection versus bridge to surgery with stenting in patients with acute right-sided colonic obstruction: a systematic review focusing on mortality and morbidity rates

Abstract: Primary resection for patients with acute RSCO seems to be associated with higher mortality and major morbidity rates than stent placement and elective resection. In addition, stent placement resulted in fewer anastomotic leakages and permanent ileostomies. However, as no high-level studies are available on the optimal treatment of RSCO and proximal stenting is considered technically challenging, future comparative studies are warranted for the development of an evidence-based clinical decision guideline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 36 publications
2
29
0
1
Order By: Relevance
“…In addition, stenting was associated with lower morbidity rates and fewer permanent stomas. These retrospective results are similar and supportive to those found is our prospective analysis 15. However, these data should be interpreted with caution, because all included studies in the systematic review were cohort studies.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, stenting was associated with lower morbidity rates and fewer permanent stomas. These retrospective results are similar and supportive to those found is our prospective analysis 15. However, these data should be interpreted with caution, because all included studies in the systematic review were cohort studies.…”
Section: Discussionsupporting
confidence: 89%
“…Ceresoli et al compared long-term oncologic outcomes of SBTS and ES in malignant left-sided colonic obstructions, and they thought there were no significant differences reported in local and overall recurrence rates [61]. Amelung et al compared procedure-related mortality and morbidity rates between primary resection and stent placement as a bridge to surgery followed by elective resection for patients with acute right-sided colonic obstruction (RSCO), and they thought primary resection for patients with acute RSCO seems to be associated with higher mortality and major morbidity rates than stent placement and elective resection [62]. Other meta-analyses compared the long-term outcomes of stents as BTS and emergency sur-gery and found that BTS was oncologically comparable with emergency surgery with respect to OS, DFS, and recurrence, and there was no difference in long-term tumour outcomes [22,[63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent multicenter retrospective study [ 169 ], the most appropriate treatment approach for patients with ORCC was evaluated, by comparing short-term postoperative outcomes and long-term oncologic outcomes after ES (emergency surgery), and BTS short-term and long-term outcomes in the BTS group were not inferior to those in the ES group. Right colon stenting is considered technically challenging and future comparative studies are needed for the development of an evidence-based recommendation for clinical decision-making [ 170 ].…”
Section: Management Of Obstruction: Right Colonmentioning
confidence: 99%